Predictors of peritoneal metastasis in gastric cancer - Capinha, Francisco Lourenço Frade (2020)
Background. Gastric cancer is the fifth most common type of cancer worldwide and one of the main factors for the decrease in overall survival and poor prognosis is the occurrence of peritoneal metastasis. This work aims to review the available literature that approaches biomarkers that can be predictors of the presence of peritoneal metastasis in these patients. Methods. This literature review was performed through searches on PubMed, identifying relevant publications related to peritoneal metastasis in gastric cancer and its predictors. Both free text and MeSH terms were employed. No past date limit was imposed and the upper limit date was February of 2020. Publications in languages other than English were excluded. Rayyan QCRI tool was used to help on the first step of eligible studies selection. A total of 209 studies were found in this first step, and only 37 were included. Additionally, the most relevant publications in the reference list of the included studies were also searched. The articles were categorized in broad categories considering the indicator they report: Tumor markers, Systemic Inflammatory Response markers (SIR markers) and Other molecular markers. Results. Regarding the tumor markers, CA125 showed the best results in serum (sCA125) and CEA was the most useful measure in the peritoneal lavages (pCEA) with a sensitivity range from 38.78% to 79.1% and 58% to 84.9%, respectively. Focusing on the SIR markers, Neutrophil to lymphocyte ratio is the one which showed consistently better results, its sensitivity ranging from 59% to 79%. The other biomarkers, most of them dependent from molecular diagnosis techniques, are less accessible not currently obtained in clinical practice and more research is needed regarding their efficacy in clinical context. The studies that combine different indicators obtained better results. This is not limited to biomarkers, tumor characteristics have also been taken into account, increasing significantly the sensitivity to detect PM in GC patients. Conclusion. Most of these biomarkers are weak predictors. The future should be about the creation and validation of clinical scores that could integrate not only some of these markers, but also tumor characteristics, imaging methods and cytological results. Largescale multicenter and stronger design studies are needed in this field, in order to produce stronger evidence about the usefulness of these biomarkers.